Dual role of thyroid hormones in rat soleus muscle MyHC isoform expression - Vadászová-Soukup, A; Soukup, T (Physiological research, 2007)
We have analyzed the influence of altered thyroid hormone levels on changes of MyHC protein isoforms and their mRNA transcripts in the soleus muscle of 2-, 4- and 7-month-old euthyroid (EU), hypothyroid (HY) and hyperthyroid (TH) female inbred Lewis strain rats (methimazole and T3 treatment started 3 to 4 weeks after birth). We have found that the content of the dominant MyHC 1 isoform gradually increased in the EU rats and that this increase was more progressive in the HY rats at all three stages. On the other hand, in the TH rats the content of MyHC 1 isoform was the highest in the 2-month-old rats and it decreased with an increasing length of T3 treatment. The content of the minor 2a MyHC isoform followed the opposite pattern. In contrast to the protein isoforms, the MyHC mRNA transcripts remained at similar levels. Nevertheless, in general, the MyHC 1 mRNA level was decreased and MyHC 2a transcript increased in the TH rats, while the opposite changes occurred in the HY rats. Our results thus suggest that in the rat soleus muscle, both increased and decreased levels of thyroid hormones speed up the formation of an adult slow phenotype which is demonstrated by the precocious appearance of the slow MyHC 1 isoform, but opposite to the hypothyroid status, a longer T3 application promotes the expression of the faster MyHC 2a isoform.
Keywords: elektroforéza v polyakrylamidovém gelu; messenger RNA; Rats; Myosin Heavy Chains; isomerie; hypertyreóza; hypotyreóza; těhotenství; hormony štítné žlázy; Muscle, Skeletal; fenotyp; Thyroid Hormones; krysa rodu Rattus; polymerázová řetězová reakce s reverzní transkripcí; Phenotype; Electrophoresis, Polyacrylamide Gel; ženské pohlaví; RNA, Messenger; zvířata; Pregnancy; kosterní svaly; Hypothyroidism; potkani inbrední LEW; Hyperthyroidism; Rats, Inbred Lew; Reverse Transcriptase Polymerase Chain Reaction; těžké řetězce myosinu; Female; Isomerism; Animals